2021
DOI: 10.3390/ani11030597
|View full text |Cite
|
Sign up to set email alerts
|

Fermented Soybean Meal Affects the Reproductive Performance and Oxidative Status of Sows, and the Growth of Piglets

Abstract: This study aimed to investigate the effect of the fermented soybean meal on the reproductive performance, oxidative stress and colostrum composition of sows, and the growth performance of their progeny. A total of 44 sows were allotted to four dietary groups (n = 11/group). The dietary groups included the basal diet group (control) and the treatment groups in which soybean meal in the basal diet was replaced with 2%, 4%, and 6% fermented soybean meal, respectively. The experimental diets were fed to the sows f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…In the current study, the measured antioxidant markers such as hepatic SOD, CAT and GSH-PX were improved, while MDA levels such as lipid peroxidation markers were decreased with the increasing level of DFSBM in their rations. In line with our results, Luo et al [ 68 ] showed that FSBM had increased muscle CAT and T-AOC in finishing pigs. Furthermore, the addition of FSBM by Bacillus spp.…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, the measured antioxidant markers such as hepatic SOD, CAT and GSH-PX were improved, while MDA levels such as lipid peroxidation markers were decreased with the increasing level of DFSBM in their rations. In line with our results, Luo et al [ 68 ] showed that FSBM had increased muscle CAT and T-AOC in finishing pigs. Furthermore, the addition of FSBM by Bacillus spp.…”
Section: Discussionsupporting
confidence: 93%
“…(2019) L. plantarum , B. subtilis MA 139, and S. cerevisiae Mixed at 1:2:2 72 h 10% inclusion replaced 38% SBM Weaning piglets Increased ADG No effect on the F:G ratio Increased total protein Lowered blood urea nitrogen Reduced piggery NH 3 levels due to nitrogen conversion Decreased piggery PM10 and PM2.5 levels Cheng et al. (2017) A. oryzae and Lactobacillus reuteri NS 48 h 2%–4% inclusion replaced up to 50% SBM Sows and piglets Attenuated gestation and lactation-associated oxidative stress by increasing serum superoxide dismutase activity and decreasing malondialdehyde, cortisol, and 8-iso-prostaglandin F2α Enhanced the average weight Improved serum estrogen and growth factors Increased colostrum protein and IgG levels Luo et al. (2021) SBM = soybean meal; FSBM = fermented soybean meal; ADG = average daily gain; FI = feed intake; ADFI = average daily feed intake; F:G = feed to gain ratio; CP = crude protein; DM = dry matter; DE = digestible energy; ME = metabolizable energy; NE = net energy; NS = not stated; IgG = immunoglobulin G; IgM = immunoglobulin M; IgA = immunoglobulin A; IL-6 = interleukin 6; IL-1β = interleukin 1β; BUN = blood urea nitrogen; LPS = lipopolysaccharide; LAB = lactic acid bacteria; NDF = neutral detergent fiber; ADF = acid detergent fiber; FCR = feed conversion ratio; ATTD = apparent total tract digestibility; AID = apparent ileal digestibility; AA = amino acid.…”
Section: Application and Emerging Health Benefits Of Fermented Soybea...mentioning
confidence: 99%
“…There is an increasing evidence that lactic acid bacteria have the ability to degrade proteins during fermentation and lactic acid bacteria with high intestinal adhesion also have antibacterial properties (Ma et al, 2022). Antioxidant, antiinflammatory and antihypertensive activities were also found in fermented soybean meal (Cui et al, 2020;Yao et al, 2021;Qi et al, 2023). Further research has shown that the fermented soybean meal can improve intestinal barrier function and reduce inflammation of piglets, which is more suitable for poultry feed and aquaculture (Cheng et al, 2019a).…”
Section: Microbial Fermentation Of Soybean Mealmentioning
confidence: 99%
“…Soybean isoflavones exist mostly as glycosides, but rarely as aglycones, which can be absorbed more easily by the intestinal wall. Luo et al (2021) showed that the fermentation of cooked soybean meal increased the content of isoflavone aglycones with high bio-conversion efficiency and reduced the total content of isoflavone glycosides by about 80%. This finding was similar to those reported by Imran et al (2018).…”
Section: Isoflavones and Polysaccharidesmentioning
confidence: 99%
See 1 more Smart Citation